Disasters, their interaction with science, technology and society - Víctor René Navarro Machado (Medisur)
The diverse methodological and theoretical approaches flourished from social sciences to carry out disasters analysis, have pointed out the necessity of taking into consideration historical conditions that have generated them and that, at the same time, have elevated the vulnerability of affected societies. The historical dimension requires studying a given topic or problem in terms of its continuity in space and time, having the possibility of making stops in its way, analysing also the event, always engulfed in a space-time context that conditions and defines it. The present work makes an analysis of the disasters in its interaction with science, technology and society.